Scheduling of unmanned aerial vehicles for supply chain networks - Nagarkar Anay Shriniwas (2014)
This report has been written with the aim of providing the reader with an overview of the author’s work and learning experience during completion of the Final Year Project at the School of Computer Engineering at Nanyang Technological University, Singapore. The objective of this report is to give the reader a detailed description and simulation of the author’s work in the scheduling of unmanned aerial vehicles in supply chain networks.